MODERN CONCEPTS OF HYPOXIA-INDUCIBLE FACTOR -1 (HIF1) AS AN IMPORTANT PATHOPHYSIOLOGICAL MECHANISM FOR THE DEVELOPMENT OF ISCHEMIA - Sayfutdinova Z.A; Xashimova G.Y; Yusupov B.N; Muhammadiev X.G; Nurillayeva G.S (European Journal of Humanities and Educational Advancements, 2023)
Hypoxia-inducible factor (HIF)-1, is a dimeric protein complex that plays an important role in the body’s response to low oxygen concentrations or hypoxia. HIF-1 is one of the main genes involved in the homeostatic process, which can increase vascularization in hypoxic areas such as localized ischemia and tumors. It is a transcription factor for dozens of target genes; HIF-1 is also important for immunological responses and is an important physiological regulator of homeostasis, vascularization, and anaerobic metabolism. In addition, HIF-1 is increasingly being studied due to its purported therapeutic potential. Because it induces angiogenesis, upregulation of this gene in patients with ischemia may promote vascular proliferation required for oxygenation. On the contrary, since HIF-1 promotes the survival and proliferation of cancer cells due to its angiogenic properties, inhibition could potentially prevent the spread of cancer. With the growing understanding of the HIF-1 pathway, inhibition and stimulation of its transcriptional activity by small molecules is currently an attractive target. Gene therapy to achieve both vascular proliferation and tumor regression has been demonstrated in animal studies but needs significant improvement and modification before it is commercially available. This review examines the potential of the HIF-1 pathway in a therapeutic intervention for diseases such as cancer and ischemia